2010
DOI: 10.22146/ijcn.17736
|View full text |Cite
|
Sign up to set email alerts
|

Pengendalian status gizi, kadar glukosa darah, dan tekanan darah melalui terapi gizi medis pada pasien diabetes mellitus (DM) tipe 2 rawat jalan di RSU Mataram NTB

Abstract: Background: The prevalence of diabetes mellitus (DM) is increasing globally, including in Indonesia. Studies by Diabetes Control and Complication Trial (DCCT) and U.K. Prospective Diabetes Study Group (UKPDS) prove the benefit of medical nutrition therapy (MNT) to glycemic control. Similar studies have not been done much in Indonesia.Objective: To identify the effects of MNT to nutrient intake, control of nutrition status, blood glucose and blood pressure of type 2 DM outpatients.Method: This was a randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…The study showed that giving pigeon pea tempeh with a 75% formulation could reduce blood glucose levels to the highest by 44.08% compared to giving tempeh pigeon peas formulations of 25% and 50%. In line with the results of the study (Yusasrini & Duniaji, 2019), which found a decrease in blood glucose levels in rats after being given pigeon pea tempeh, from 323.68 mg/dl to 200.37 mg/dl Research on giving pigeon pea tempeh milk mixed with ginger to people with diabetes was reported (Suhaema & Cahyaningrum, 2017), with the result that there was a significant decrease in fasting blood glucose levels, namely from 207.3 mg/dL and 186.6 mg/dL ( p = 0.026. Likewise, subsequent studies which gave a drink from a mixture of pigeon pea powder, ginger, and cinnamon resulted that fasting blood glucose levels decreasing from 227.3 mg/dl to 167.7 mg/dl after 14 days of intervention (Suhaema & Abdi, 2018).…”
Section: Discussionsupporting
confidence: 78%
“…The study showed that giving pigeon pea tempeh with a 75% formulation could reduce blood glucose levels to the highest by 44.08% compared to giving tempeh pigeon peas formulations of 25% and 50%. In line with the results of the study (Yusasrini & Duniaji, 2019), which found a decrease in blood glucose levels in rats after being given pigeon pea tempeh, from 323.68 mg/dl to 200.37 mg/dl Research on giving pigeon pea tempeh milk mixed with ginger to people with diabetes was reported (Suhaema & Cahyaningrum, 2017), with the result that there was a significant decrease in fasting blood glucose levels, namely from 207.3 mg/dL and 186.6 mg/dL ( p = 0.026. Likewise, subsequent studies which gave a drink from a mixture of pigeon pea powder, ginger, and cinnamon resulted that fasting blood glucose levels decreasing from 227.3 mg/dl to 167.7 mg/dl after 14 days of intervention (Suhaema & Abdi, 2018).…”
Section: Discussionsupporting
confidence: 78%